2007
DOI: 10.1080/09297040600888753
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Working Memory in School-aged Children ExposedIn Uteroto Cocaine

Abstract: Children exposed in utero to cocaine exhibit a possible impairment in procedural learning and diminished efficiency in creating and accessing an internal spatial map to master the hidden maze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
4
38
0
1
Order By: Relevance
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…However, these structures are involved in multiple processes (and the reduced responses observed were not constrained to only these regions); thus the larger developmental implications of these findings remains to be determined. For example, given the role of the striatum in habit formation and learning, these findings might relate to the working memory deficits (Mayes et al, 2007) reported among children with PCE. Similarly, reductions in PFC activations may relate to previously reported impairments in response inhibition (Accornero et al, 2007), which could influence multiple developmental processes (such as the appropriate inhibition of negative or anxiety-provoking thoughts or actions) other than substance-use initiation.…”
Section: Developmental Implicationsmentioning
confidence: 99%
“…Prenatal cocaine exposure (PCE) is associated with negative behaviors during early childhood, including externalizing and behavioral problems (Ackerman et al, 2010) and poor sustained attention (Ackerman et al, 2010), inhibitory control (Bridgett and Mayes, 2011) and working memory (Mayes et al, 2007). By contrast, effects of PCE during adolescence and young adulthood may be more subtle than those observed during early childhood and are less well understood (Buckingham-Howes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…190,[242][243][244][245][246][247][248][249][250] However, several studies have revealed alterations in various aspects of executive functioning, 221,241 including visual-motor ability, 244 attention, [251][252][253] and working memory. 254 To date, limited data are available revealing an association between prenatal methamphetamine exposure and IQ. 255 …”
Section: Behaviormentioning
confidence: 99%